RUNX2 Mediates Renal Cell Carcinoma Invasion through Calpain2 - Zhang, Xiaoyu; Wei, Shufei; Ren, Zongtao; Liu, Bin (Biological & pharmaceutical bulletin, 2022)
Runt-related transcription factor 2 (RUNX2), a specific transcription factor of osteocytes, has been confirmed to be involved in the malignant biological behavior of various tumor cells, including renal cell carcinoma. However, the mechanism of action of RUNX2 in renal cell carcinoma cells is not yet fully understood. In this study, RUNX2-negative A498 cells and strongly positive ACHN cells were selected as the study subjects. An invasion chamber assay was used to detect the invasive ability of the cells. The expression of each protein was detected by Western blotting or immunofluorescence assays. The invasive ability of A498 cells was enhanced after the expression of RUNX2 protein was upregulated, whereas ACHN cells decreased after the expression of RUNX2 protein was silenced. The expression of calcium-activated neutral protease 2 (Calpain2) and fibronectin (FN) proteins was upregulated in A498 cells overexpressing RUNX2 protein, whereas it was downregulated after the downregulation of RUNX2 protein expression in ACHN cells. It was found that Calpain2 small interfering RNA (siRNA) or calpain inhibitor calpeptin could inhibit the expression of FN in ACHN and A498 cells overexpressing RUNX2. Calpain2 siRNA or calpeptin inhibited the invasion of A498 cells overexpressing RUNX2. Similarly, in ACHN cells, Calpain2 siRNA or calpeptin inhibited cell invasion. RUNX2 upregulates FN protein expression via Calpain2, thereby mediating renal cell carcinoma invasion.